From Android games to coding in C—An approach to motivate novice engineering students to learn programming: A case study - Dolgopolovas, Vladimiras; Jevsikova, Tatjana; Dagiene, Valentina (Computer applications in engineering education, 2018)
This paper deals with the problem of overcoming difficulties and raising the motivation of novice engineering students studying programming. We consider this an important factor for engineering education in general and for programming of embedded devices, as well as for calculations and modeling in the field of scientific computing in particular. We present a case study on how novice engineering students can be motivated to study structured programming and coding in C using game programming in the App Inventor environment. The study is based on the authors’ practical teaching experience in the Applied Sciences University for novice programmers, with students of the Technology of Smart Devices specialty, as well as the authors’ long‐time research activities in teaching Computer Science.